2019
DOI: 10.1111/jgh.14658
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pancreatic cystic lesions detected by magnetic resonance imaging in the Chinese population

Abstract: Background and Aim Incidental pancreatic cystic lesions (PCLs) are being diagnosed more frequently. However, little is known about the prevalence of PCLs in the Chinese population. The aim of the study was to assess the crude prevalence of PCLs in individuals who underwent magnetic resonance imaging (MRI). Methods Data from consecutive patients who underwent MRI without pancreatic indications were included. MRI images were reviewed for the presence of pancreatic cysts. The prevalence of PCLs and high‐risk PCLs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 44 publications
6
18
2
Order By: Relevance
“…A recent meta‐analysis reported that the pooled prevalence of incidental PCLs was 8% and four times higher in studies conducted in the USA than in Asia . The prevalence of PCLs in our study group was 1.0%, which is lower than that reported in previous studies (1.9–2.1%) . First, small cysts that were not detected in the past may be underestimated as the keyword search was performed using a computerized system.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…A recent meta‐analysis reported that the pooled prevalence of incidental PCLs was 8% and four times higher in studies conducted in the USA than in Asia . The prevalence of PCLs in our study group was 1.0%, which is lower than that reported in previous studies (1.9–2.1%) . First, small cysts that were not detected in the past may be underestimated as the keyword search was performed using a computerized system.…”
Section: Discussioncontrasting
confidence: 71%
“…Pancreatic cystic lesions (PCLs) are important incidental findings in a diverse range of disease entities of both indolent and malignant evolution, depending on their subtypes . PCLs are detected in 1.9–2.1% of the patients on computed tomography (CT) and in 13.5–49.1% of the patients on magnetic resonance imaging, with the incidence increasing with age . Although various investigations into the progression rate and malignancy risk of PCLs have been previously reported, most studies only focused on definite or presumed branch duct intraductal papillary mucinous neoplasms (IPMNs).…”
Section: Introductionmentioning
confidence: 99%
“…Referring to the results obtained in our study, the incidence of cystic lesions in the examined population was significantly higher in patients over 50 years old. This observation is consistent with a study, published in 2019, on a large population (10 987) of patients who underwent magnetic resonanace imaging (MRI) for reasons other than pancreatic disease [21]. In this research, similarly to ours, a strong relationship between the incidence of cystic lesions in the pancreas and the age of patients was observed.…”
Section: Discussionsupporting
confidence: 93%
“…Pancreatic cystic lesions (PCLs) are being detected more frequently because of the advancements in radiological technologies. Their prevalence ranges from 1.9% to 49.1% in different races . Surgical resection of PCLs with invasive carcinoma (IC) and high‐grade dysplasia (HGD) is generally the accepted treatment method .…”
Section: Introductionmentioning
confidence: 99%